1998
DOI: 10.1007/s002560050413
|View full text |Cite
|
Sign up to set email alerts
|

Internal derangement of the knee after ipsilateral femoral shaft fracture: MR imaging findings

Abstract: There is a common incidence of both ligamentous and meniscal injury to the knee after ipsilateral femoral shaft fracture. MR imaging can be useful in assessing the extent of injury, and may reveal findings unsuspected after clinical examination of the knee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Generally, it has been reported that a high incidence of internal knee injuries occurs in conjunction with ipsilateral femoral shaft fractures, but the incidence of knee injuries associated with tibial shaft fracture is lower than that of femoral shaft fracture [5][6][7][8][9]. Moreover, there has been no report on a case with ACL tear and depressed marginal fracture of the posteromedial tibial plateau combined with tibial shaft fracture like this case.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Generally, it has been reported that a high incidence of internal knee injuries occurs in conjunction with ipsilateral femoral shaft fractures, but the incidence of knee injuries associated with tibial shaft fracture is lower than that of femoral shaft fracture [5][6][7][8][9]. Moreover, there has been no report on a case with ACL tear and depressed marginal fracture of the posteromedial tibial plateau combined with tibial shaft fracture like this case.…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, a depressed fracture of the posteromedial plateau concomitant with an ACL tear is a relatively uncommon lesion although it is one of several osseous lesions around the tibial plateau associated with an ACL injury [10][11][12][13]. These lesions are generally difficult to detect owing to the diagnostic limitations of conventional radiographs [5]. Moreover, the dramatic presentation of high-energy mechanism fracture of tibial shaft tends to mask other associated knee injuries [7,9].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a recent radiologic investigation by Blacksin et al, 1 an MRI was performed on 34 patients with femoral shaft fractures. Knee pain at time of the fracture, swelling of the knee, effusion or an examination under anesthesia suspicious for ligament instability were the indications for MRI.…”
Section: Undetected Injuries To the Knee Accompanying Fracturementioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Pedersen and Serra 5 in 1968 were the first to point out that serious injury to the major ligaments of the ipsilateral knee can occur with femoral shaft fractures. Since then, several authors have underlined the importance of physical examination of the knee with an ipsilateral femur fracture because they recognized delays in diagnosis of such injuries.…”
mentioning
confidence: 99%